Pancreaticobiliary Maljunction Is Associated with Common Bile Duct Carcinoma: A Meta-Analysis - Yang Li; Jun Wei; Zhongxin Zhao; Tiangeng You; Mingan Zhong (The Scientific World Journal)
Objective. Pancreaticobiliary maljunction (PBM) has been reported to be associated with an increased risk of gallbladder carcinoma. However, the relationship between PBM and common bile duct carcinoma (CBDC) remains unclear. We aimed to conduct a meta-analysis to determine the available evidence on the association between PBM and CBDC. Methods. The pooled odds ratio (OR) and standard mean differences (SMD) with 95% confidence interval (95% CI) were used to estimate the effects. Results. A total of eight case-control studies and two cohort studies were identified. The incidence of PBM was higher in CBDC patients than in controls (OR=1.45; 95% CI, 1.19–1.76). Compared with patients without PBM, CBDC patients with PBM were younger at the diagnosis age (SMD=−0.46; 95% CI, −0.64 to −0.28). A difference in the incidence of associated CDC was found between CBDC patients with or without PBM (OR=2.14; 95% CI, 1.60–2.87). Conclusions. Compared with benign biliary tract diseases, the incidence of PBM was higher in CBDC patients, especially in relatively young patients. We also found that the incidence of CDC was higher in CBDC patients with PBM. These findings showed positive association between PBM and CBDC, which may help in identifying high-risk individuals.